Falling for autumn ebook - Dean, James (Pete the Cat., 2020)
New York Times bestselling creators James and Kimberly Dean show us all the wonderful things about autumn. A great book to share with the family at Thanksgiving or anytime! Pete the Cat isn't sure about the changing of the seasons from summer to autumn. But when he discovers corn mazes, hay rides, and apple picking, Pete realizes there's so much to enjoy and be thankful for about autumn.